Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5603/kp.a2017.0035
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk reduction in sedentary postmenopausal women during organised physical activity

Abstract: A b s t r a c tBackground: Cardiovascular (CV) diseases are a major cause of death in elderly women. Aerobic training improves component CV risk factors. Long-term, higher-intensity, group-based and home-based exercise training has been shown to improve exercise performance. However, it is not clear if short-term, group-based or home-based training with an educational programme permanently improves cardiometabolic parameters in elderly women. Aim:The aim of the study was to evaluate the effectiveness of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
3
7
0
3
Order By: Relevance
“…To sum up the discussion, it should be emphasized that the applied daily outpatient care and comprehensive rehabilitation program including tailored endurance training, psychological therapy and other forms of therapeutic interactions proved effective in reducing the risk of falls, improving the balance and gait efficiency, and minimizing the severity of pain experienced by respondents. The results confirm that, where possible, geriatric rehabilitation should include elements of systematic and intensive physical activation in the form of endurance training that improves the functioning of skeletal muscles, cardiovascular and respiratory systems, and also positively affects the activities of the central nervous system [21][22][23]. 9.08/16.00 points (SD=3.64), and after its completion it was graded at 12.47/16.00 points (SD=4.14).…”
Section: Resultssupporting
confidence: 64%
“…To sum up the discussion, it should be emphasized that the applied daily outpatient care and comprehensive rehabilitation program including tailored endurance training, psychological therapy and other forms of therapeutic interactions proved effective in reducing the risk of falls, improving the balance and gait efficiency, and minimizing the severity of pain experienced by respondents. The results confirm that, where possible, geriatric rehabilitation should include elements of systematic and intensive physical activation in the form of endurance training that improves the functioning of skeletal muscles, cardiovascular and respiratory systems, and also positively affects the activities of the central nervous system [21][22][23]. 9.08/16.00 points (SD=3.64), and after its completion it was graded at 12.47/16.00 points (SD=4.14).…”
Section: Resultssupporting
confidence: 64%
“…To sum up the discussion, it should be emphasized that the applied daily outpatient care and comprehensive rehabilitation program including tailored endurance training, psychological therapy and other forms of therapeutic interactions proved effective in increasing the involvement of seniors in physical activity and minimizing the severity of depression symptoms experienced by the subjects. The results confirm that, where possible, geriatric rehabilitation should include elements of systematic and intensive physical activation in the form of endurance training that improves the functioning of musculoskeletal, cardiovascular and respiratory systems, and also positively affects the activities of the central nervous system [21,22].…”
Section: Discussionsupporting
confidence: 64%
“…This category consists of seven publications [10][11][12][13][14][15][16] that address the effects of exercise on the metabolism of menopausal women. The authors mainly focused on the endocrine metabolism and the normalization of the body's hormones in order to improve the well-being of women under these conditions.…”
Section: The Influence Of Physical Exercise On the Metabolism Of Postmentioning
confidence: 99%
“…The authors mainly focused on the endocrine metabolism and the normalization of the body's hormones in order to improve the well-being of women under these conditions. Of the articles analyzed, four [10][11][12][13] addressed the contributions of physical exercise to the lipid metabolism, the reduction of waist circumference and weight loss. One study 11 demonstrated that regular exercise training over a three-month period resulted in a significant improvement in metabolic parameters, with a significant increase in HDL level, a significant reduction in LDL level, improved physical fitness and heart rate and diastolic blood pressure normalization, reducing cardiovascular risks over ten years when analyzed by the Framingham scale 10,11 . In addition, the studies 14,15 highlighted that performing exercise as a non-pharmacological intervention is a valuable therapeutic resource in postmenopausal women, acting positively in reducing visceral adipose tissue, waist circumference and BMI.…”
Section: The Influence Of Physical Exercise On the Metabolism Of Postmentioning
confidence: 99%